Characterization and identification of some probiotic properties of lactic acid bacteria isolated from curdled cow and goat milk - patil, gunjan (Indian Journal of Dairy Science, 2024)
Since ancient times, curd is the most common fermented milk product consumed in India. Curd comprises brilliant gut healers that improves immune system. Raw milk of cow and goat is rich in various nutrients, minerals and vitamins. Additionally, it also contains mixture of probiotic lactic acid bacteria (LAB). Widespread use of synthetic antimicrobial agents causes resistance of infectious microbes to these compounds. For this reason, identification of natural antimicrobials like LAB appears to be essential for prevention and treatment. The purpose of this article is to isolate and identify probiotic LAB acquiring safety aspects from curd. The samples are set by natural curdling of raw milk collected from cow and goat. Gram positive and catalase negative LAB were isolated from curd samples. A total of 22 isolates were presumed as LAB form the curdled milk samples collected aseptically. Primarily these isolates were screened for cultural, microscopic and biochemical characteristics. Selected LAB strains were exposed to in vitro gastrointestinal conditions like low pH, bile salt, fluctuating NaCl and phenol conditions. Also, these isolated strains were evaluated for survival in stimulated gastric juice and stimulated intestinal juice. Further, safety property of these isolates was checked by their haemolytic, deoxyribonuclease (DNase) activity and susceptibility to antibiotics. On the basis of the evaluated results isolates showing prominent probiotic activities were further subjected for molecular identification. In conclusion Lactiplantibacillus plajomi, Enterococcus italicus and Lactobacillus pentosus are identified as LAB possessing impressing probiotic properties.